Linguistic foundations of language teaching - Cáceres Estaña, Marlene (2018)
This work has been divided into seven chapters. Chapter I has to do with Linguistic Structuralism and the Audiolingual Method of Language Teaching. Chapter Two focuses on Generative linguistics and language teaching and Chapter Three develops Functional linguistics and language teaching. Also Chapter IV develops topics referred to pragmatics and language teaching. Chapter V has to do with Text Linguistics and Language Teaching to end with the development of linguistic foundations of the Communicative Language Teaching in Chapter VI. Finally, we develop the didactic application of the topic where we present a lesson plan about a point of the linguistic foundations of language teaching.